LITERATURE STUDY: ANALYSIS OF EFFORTS TO IMPROVE MATHEMATICAL LOGIC INTELLIGENCE IN EARLY CHILDHOOD - Amalia Nugraha Fisabilila; Juan Febri Adi Prayogo; Rosi Maulidya Ardhana; Conny Dian Sumadi (Citra Dharma Cindekia, 2022)
This study aims to determine the increase in mathematical logic intelligence in early childhood through several efforts that can be used by teachers. This research is a literature study with a descriptive qualitative research type that seeks to describe any efforts that can improve mathematical logic intelligence in early childhood. In this study, the authors used references in the form of 10 relevant scientific articles published from various national journals. The results of the study show that mathematical logic intelligence can be improved through various forms of effort. Among them, the first is by using game methods such as snakes and ladders games, smart bottle cap games, number card games, bingo games, and numbering games. Second, by using learning media such as media relia and flannel board media. Third, by using activities such as science-based learning, fun cooking activities, and bibliotherapy for children. The conclusion in this study that there are various efforts that can be used by teachers in improving mathematical logic intelligence.